Pembelajaran balaghah berbasis IT dengan aplikasi WhatsApp di Pondok Pesantren Anwarul Huda - Ulloh, Faidhul Mahdhi Ala’ (Maliki Interdisciplinary Journal, 2024)
The second semester of Balaghah at Anwarul Huda Islamic Boarding School lasts about an hour and uses the book Jauharul Maknun. The teachers face a great deal of difficulty because of the short class period because they have to cover a lot of difficult subject. To address this issue, effective learning materials are thus required. To ensure efficient and effective learning, teachers might utilize WhatsApp as a teaching tool. The purpose of this study is to look at how Balaghah in second-grade at Anwarul Huda Islamic Boarding School in Malang uses WhatsApp as a learning tool. A case study technique is used in conjunction with qualitative research as the research methodology. There are several steps involved in data analysis, such as gathering data, reducing data, presenting data, and coming to conclusions or doing verification. According to the research’s conclusions, WhatsApp is utilized in the Balaghah study to explain the book’s meaning, summarize its contents, offer instances, and address them. Using WhatsApp as a teaching tool has several benefits, such as effective instruction, flexible access to resources, and a rise in student involvement in the classroom. The uniformity of shared materials and the requirement for greater self-discipline on the part of students while using WhatsApp for studying are two obstacles to overcome when utilizing the messaging app as a learning tool.